2006
DOI: 10.3139/217.0090
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Take-up Speed of Melt Spinning on the Structure and Mechanical Propertiesof Maximally Laser Drawn PA9-T Fibers

Abstract: A new semiaromatic polyamide, PA9-T, was melt-spun at takeup speeds from 200 to 1000 m min -1 . The as-spun fibers were drawn with CO 2 laser-heated drawing to their maximal draw ratio (DR max ). The drawing stress was recorded during this process. The effects of take-up speed of melt-spinning on maximally drawn fibers were characterized through measurements of density, birefringence, wide-angle X-ray diffraction, crystal orientation, tensile testing, and dynamic viscoelastic analysis. All as-spun fibers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…For example, Cakir et al [19] reported that a semi-aromatic polyamide chain could be incorporated into the PA6 chain via solid-state polymerization of a semi-aromatic nylon salt and PA6. Han et al [20] used e-caprolactam, semi-aromatic salt of terephthalic acid, and hexamethylene diamine as raw materials to obtain a copolyamide PA(6-co-6T) via solution copolymerization. A similar approach has been proposed to prepare a copolymer of PA66 and PA6T (PA(66-co-6T)) via copolymerization of adipic acid (ADA), terephthalic acid (PTA), and hexamethylenediamine (HMDA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Cakir et al [19] reported that a semi-aromatic polyamide chain could be incorporated into the PA6 chain via solid-state polymerization of a semi-aromatic nylon salt and PA6. Han et al [20] used e-caprolactam, semi-aromatic salt of terephthalic acid, and hexamethylene diamine as raw materials to obtain a copolyamide PA(6-co-6T) via solution copolymerization. A similar approach has been proposed to prepare a copolymer of PA66 and PA6T (PA(66-co-6T)) via copolymerization of adipic acid (ADA), terephthalic acid (PTA), and hexamethylenediamine (HMDA).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a semi-aromatic polyamide, which is a combination of aromatic and aliphatic moieties, has attracted more and more attention in the past two decades. [4][5][6][7] Nowadays, many companies such as BP Amoco, [8] DSM, [9] and Solvay [10] have produced some commercial semi-aromatic polyamides including poly(hexamethylene terephthalamide) (PA6T), [11] poly(nonamethylene terephalamide) (PA9T), and so on. However, their degradation temperatures are relatively close to their melting temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, semiaromatic polyamide is considered to be a high‐performance material because of its high‐temperature dimensional stability, corrosion‐resistance properties, and low moisture uptake. However, only a few semiaromatic polyamides, such as poly(nonamethylene terephthalamide), poly(decamethylene terephthalamide), and copolymer poly(hexamethylene terephthalamide)‐ co ‐poly(hexamethylene hexanediamide) (PA6T/66) and poly(hexamethylene terephthalamide)‐ co ‐polycaprolactam (PA6T/6) copolymers, are commercial and processable because it is difficult to account for their thermal performance and processability simultaneously. In our previous study, we introduced aliphatic linkages or thioether units into the semiaromatic polyamide main chain as flexible segments to improve its processability .…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the thermal properties of aliphatic polyamides, the incorporation of aromatic units into the polymer main chain acts as an efficient approach. 10 However, only a few semi-aromatic polyamides, such as the copolymer of PA6T, 11 poly(nonamethylene terephthalamide) (PA9T), [12][13][14][15] poly(decamethylene terephthalamide) (PA10T), the product of Dupont, Solvay, Mitsui, Evonik and so on, are commercially available. 8) and Aramid-1313 (ref.…”
Section: Introductionmentioning
confidence: 99%